PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada Perusahaan yang Tercatat di Bursa Efek Indonesia) - Arifani, Rizky (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study examined the effect of corporate governance on financial performance of the company. Good corporate governance was identified by the number of audit committee, the proportion of managerial ownership, the proportion of institutional ownership, and the proportion of independent commissioners. Indicators of financial performance were measured by return on equity (ROE). The sample used 186 companies from a population of 347 companies listed on the Indonesian Stock Exchange which issuedÂ  GCG reports with total of observation data 372 in period 2010-2011. The sample was determined using proportionate sampling method. The study used multiple regression analysis and processed using SPSS. The results showed that there was significant effect between audit committees, institutional ownership, and independent commissioner to financial performance. However it was not found that managerial ownership had an influence on financial performance. Keywords: good corporate governance, financial performance, return on equity (ROE)